"Most of them are junk food but we did put fruit on there and we have water". Issue 2 (2nd February 2015) - Waddingham, Suzanne; Stevens, Stella; Macintyre, Kate; Shaw, Kelly
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The Australian Dietary Guidelines support good health and disease prevention. Children with healthy eating habits established early in life have been shown to continue these habits into adulthood compared with those children who have poor eating habits in their younger years. The nutritional intake of many Australian children is not in accordance with the national guidelines. The reasons children make the food choices they do are unclear from the literature. The paper aims to discuss these issues. Design/methodology/approach – This study used participatory action research methods to explore why primary school-aged children make the food choices that they do. A non-government primary school requested assistance in encouraging their children to make healthier choices from the school canteen menu. The authors gathered opinions from the children in two different ways; a group discussion during class and a "discovery day" that involved four class grades. The authors identified children's food preferences and food availability in canteens. The authors explored how the children perceived healthy foods, the importance of a healthy food environment and what criteria children use to decide what foods to buy. Findings – Children's food preferences were mostly for unhealthy foods, and these were readily available in the canteen. The perception about what foods were healthy was limited. Despite being asked to develop a "healthy" menu, the majority of choices made by the children were not healthy. Children described unhealthy choices as preferable because of taste of the food, if it was sugary, if it was quick to eat, available and cheap, the relationship of food and weather, the connection to health conditions and peer dominance. Practical implications – This study suggests that children make their food choices based on simple concepts. The challenge lies around producing healthy options in collaboration with the school community that match the children's food choice criteria. Originality/value – This paper provides a modern and inspiring whole school approach based on equity and empowerment of the children. Discovering why children make food choices from the children's perspective will help to present healthy options that will be more appealing for children. The methodology used to uncover why children make their food choices has also provided valuable insight into a study design that could be used to address other childhood research questions. The methodology offers an educative experience while gathering rich information directly from the children. This information can be used by the school to support children to have more control over their health and to develop behaviours to increase their health for the rest of their lives.